Physical and chemical processes in the aquatic environment - Christensen, Erik R., 1943-; Li, An, 1952- (Hoboken, New Jersey : Wiley, 2014)
'This book has a unique outline in that it follows pollution from sources to impact. Included in the text is the treatment of various tracers, ranging from pathogens to stable isotopes of elements and providing a comprehensive discussion which is lacking in many other books on pollution control of natural waters'-
Includes bibliographical references and index.
Keywords: Water -- Pollution; Water chemistry